2015
DOI: 10.1177/1534735415580678
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Therapy and Counseling Support for Women With Breast Cancer

Abstract: Background. Animal-assisted therapy (AAT) interventions have been shown to assist in coping and improve patient responses to symptoms. Specifically, the presence of an animal has been found to lower anxiety and motivate participation in therapy. We aimed to explore the acceptability of and experience of AAT during individual breast cancer counseling sessions. Methods. Patients undertaking counseling with a therapy dog present were invited to participate in the study. Patients were individually interviewed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…In contrast to medication, prior experiences with dogs as pets had little effect on the acceptability of TF‐CBT, with and without the addition of CAT. While this supports suggestions of prior research that there is a generalised tendency towards acceptance of AAT (e.g., White et al, ), it also contradicts others studies which suggested that a client's attitude towards CAT might hinge on their perceptions of, and prior experiences with, dogs (Black et al, ; Yap et al, ). These worries are not necessarily groundless; many individuals dislike interacting with dogs (Lefkowitz et al, ; Muris, Van Zwol, Huijding, & Mayer, ).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In contrast to medication, prior experiences with dogs as pets had little effect on the acceptability of TF‐CBT, with and without the addition of CAT. While this supports suggestions of prior research that there is a generalised tendency towards acceptance of AAT (e.g., White et al, ), it also contradicts others studies which suggested that a client's attitude towards CAT might hinge on their perceptions of, and prior experiences with, dogs (Black et al, ; Yap et al, ). These worries are not necessarily groundless; many individuals dislike interacting with dogs (Lefkowitz et al, ; Muris, Van Zwol, Huijding, & Mayer, ).…”
Section: Discussionsupporting
confidence: 69%
“…Studies of the acceptability of AAT amongst lay or consumer populations are even rarer representing a significant gap in the literature. What studies do exist have mostly utilised qualitative methods, examining the opinions of individuals following participation in an intervention program (e.g., Stoffel & Braun, ; White et al, ). Whilst the feedback has been overwhelmingly positive, generalisability remains a concern.…”
mentioning
confidence: 99%
“…This may in part be due to a gap in evidence or in evidence failing to inform or reach practitioners and policy makers responsible for care planning arrangements. Whilst the benefits of formalised AAT for conditions such as dementia [18, 19], cancer [20, 21] and childhood developmental disorders [22, 23] are gaining recognition, there is currently a lack of evidence exploring the contribution of pets in the broader context of support networks and the role they may play in recovery-orientated activities and the management of mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Related, people who have experienced a 'close brush with death,' such as a terminal diagnosis of cancer, report high levels of appreciation for being in nature to reorient and find some semblance of peace in their life (Martin & Kleiber, 2005). Those who receive benefit from exposure to natural environments, and are also comforted by the company of dogs, may find the synthesis of therapeutic natural landscapes with a dog to be of significant value to their state of being, regardless of their health prognosis (White et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dogs have been called 'social lubricants' (Moody, Maps, & O'Rourke, 2002) for their uncanny ability to help people with serious illnesses and trauma find brief moments of catharsis (Browder, 2009), create meaningful relationships when there are none (Fox & Gee, 2017) and connect with healthcare providers (White et al, 2015). In this paper, the therapeutic qualities of human-dog interactions in natural environments will be demonstrated by focusing on one woman's terminal cancer diagnosis while in end-of-life care (Engleman, 2013).…”
Section: Introductionmentioning
confidence: 99%